Politics of protest in hybrid regimes : managing dissent in post-communist Russia - Robertson, Graeme B. (Cambridge University Press, 2011)
"Since the end of the Cold War, more and more countries feature political regimes that are neither liberal democracies nor closed authoritarian systems. Most research on these hybrid regimes focuses on how elites manipulate elections to stay in office, but in places as diverse as Bolivia, Georgia, Kyrgyzstan, Serbia, Thailand, Ukraine, and Venezuela, protest in the streets has been at least as important as elections in bringing about political change. The Politics of Protest in Hybrid Regimes builds on previously unpublished data and extensive fieldwork in Russia to show how one high-profile hybrid regime manages political competition in the workplace and in the streets. More generally, the book develops a theory of how the nature of organizations in society, state strategies for mobilizing supporters, and elite competition shape political protest in hybrid regimes"--Provided by publisher.